Tradução e adaptação transcultural da versão pediátrica do banco de itens de Impacto da Asma do Patient-Reported Outcomes Measurement Information System (PROMIS® Pediátrico) para a língua portuguesa - Menezes, Tathiana Tavares (2017)
Introduction: Patient-Reported Outcomes (PRO) instruments have been recognized as key measures for assessing the treatment of chronic diseases over the last decade. In asthma, the correlation between scores of its symptoms and the quality of life of patients with the disease is observed. Objective: This study aimed to transculturally translate and adapt into the Portuguese language of Brazil the pediatric version of the Patient-Reported Outcomes Measurement System (PROMIS®) Asthma Impact Bank, which evaluates its intensity and perception of symptoms in children and adolescents. Materials and Methods: The scale has been translated to international standards according to the guidelines of the Functional Assessment of Chronic Illness Therapy (FACIT). Results: The Brazilian version of the PROMIS® Asthma Impact Bank has been finalized and will be in the process of validating its psychometric properties so that it can be used as an instrument for investigation and research of selfreported symptoms for pediatric patients diagnosed with asthma. Conclusion: The initial objective of transcultural translation and adaptation was achieved, as the target items maintained the semantic, conceptual and cultural equivalence proposed in the source items. The scale is available to be validated, thus demonstrating the measurement properties required for the intended application. It will be another important resource in the assessment of patients with asthma, in relation to the treatment’s intended well-being.